2021
DOI: 10.1002/adom.202100101
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging and Optical Trapping: Complementary Tools for Assessing Direction‐Dependent Polarized Emission from Single Upconverting LiYF4:Yb3+/Er3+ Microparticles

Abstract: Single‐particle fluorescent probes with the capacity to infer specific intracellular conditions, for instance, have great application potential in the realm of biomedicine. Imaging techniques that improve our understanding of the fluorescence processes at a single‐particle level are thus instrumental in actualizing this potential. This study demonstrates the importance of implementing synergistic single‐particle spectroscopic techniques to gain a more comprehensive understanding of the optical anisotropy exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [ 107–111 ] To make use of polarized UCL, Paloma et al. reported using microsized upconverting particles (UCP) to monitor the suspending medium in real‐time via single‐particle spectroscopy.…”
Section: Remote Regulation Of Upconversionmentioning
confidence: 99%
“…Similarly, the combination of SPPS and optical tweezers allowed gaining insight into the spatial variations in the emission intensities of a thick film of UCNPs obtained by hyperspectral imaging. In the hyperspectral analysis of 36 neutrally (θ = 56°, θ is the angle relative to its optic axis) and 35 non-neutrally oriented (0° ≤ θ ≤ 90°; θ ≠ 56°) LiYF 4 :Yb 3+ /Er 3+ microparticles, the averaged intensities of both the green and red emissions stemming from the latter particles were found to be nearly 2 times higher than the former ones . Using an optical beam, one can further trap single LiYF 4 :Yb 3+ /Er 3+ microparticles in three different spatial orientations, which allowed for its polarized emission to be probed at two different angles, θ = 56° and 90°.…”
Section: Current Implementation Of Upconverting Nanoparticles In Stim...mentioning
confidence: 99%
“…In the hyperspectral analysis of 36 neutrally (θ = 56°, θ is the angle relative to its optic axis) and 35 non-neutrally oriented (0°≤ θ ≤ 90°; θ ≠ 56°) LiYF 4 :Yb 3+ /Er 3+ microparticles, the averaged intensities of both the green and red emissions stemming from the latter particles were found to be nearly 2 times higher than the former ones. 33 Using an optical beam, one can further trap single LiYF 4 :Yb 3+ /Er 3+ microparticles in three different spatial orientations, which allowed for its polarized emission to be probed at two different angles, θ = 56°and 90°. Recently, the crystal-field (CF) polarization components of a class of bipyramidal LiLuF 4 :Yb 3+ /Er 3+ microcrystals with a mean size of ∼20 μm × 12 μm has been determined by SPPS.…”
Section: Nanoparticles In Stimuli Sensingmentioning
confidence: 99%
“…Lanthanide (Ln 3+ )-doped upconversion (UC) materials, which have exhibited large anti-Stokes shifts, high photochemical stability, and adjustable emission, have proven to be excellent optical probes. A few reports have revealed the polarized UC from a single particle or assembly with an orderly alignment. Compared with the assembly, a single particle is particularly desired for the polarization studies to obtain highly polarized UC emission and explore further applications. It is found that the DOPs of the 3 H 4 → 3 H 6 and 1 G 4 → 3 H 5 transitions of Tm 3+ from a single NaYF 4 :Yb/Tm nanorod were both close to 1 .…”
mentioning
confidence: 99%